2007
DOI: 10.1086/514809
|View full text |Cite
|
Sign up to set email alerts
|

350 μm Observations of Ultraluminous Infrared Galaxies at Intermediate Redshifts

Abstract: We present 350 m observations of 36 ultraluminous infrared galaxies ( ULIRGs) at intermediate redshifts (0:089 z 0:926) using the Submillimeter High Angular Resolution Camera II (SHARC-II) on the Caltech Submillimeter Observatory (CSO). In total, 28 sources are detected at S/ N ! 3, providing the first flux measurements longward of 100 m for a statistically significant sample of ULIRGs in the redshift range 0:1 P z P 1:0. Combining our 350 m flux measurements with the existing IRAS 60 and 100 m data, we fit a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 42 publications
4
64
0
Order By: Relevance
“…Sanders & Mirabel 1996;Elbaz et al 2010). Yang et al (2007) have observed seven of our objects at 350 μm and derive more precise temperatures, which are very similar to the values computed above. We note a clear increase in the dust temperatures with respect to our 0.2 < z < 0.6 sample in Paper II.…”
Section: Molecular Gas Excitationsupporting
confidence: 86%
“…Sanders & Mirabel 1996;Elbaz et al 2010). Yang et al (2007) have observed seven of our objects at 350 μm and derive more precise temperatures, which are very similar to the values computed above. We note a clear increase in the dust temperatures with respect to our 0.2 < z < 0.6 sample in Paper II.…”
Section: Molecular Gas Excitationsupporting
confidence: 86%
“…Although to test this one needs both robust measurements of the T d (based on observations that probe the peak of the SED of the galaxies) and to have a large sample of LBGs, the upper limits that we derived in this study can provide a first insight. Clements et al (2010) and Yang et al (2007). In all these studies, the T d was measured in manner that is similar to ours, fitting modified black-body models with fixed β=1.5 to the FIR photometric points of each sample, hence the comparison between these studies and our sample is meaningful.…”
Section: Comparison With Smgsmentioning
confidence: 95%
“…We note that these values correspond to 3σ upper and lower T d limits for IRAC and MIPS LBGs. Included are results for 0<z<0.98 ULIRGs (blue filled triangles, Clements et al 2010, Yang et al 2007). The green shaded region depicts the loci of high-z SMGs by Chapman et al (2005), while the orange shaded area shows the 2σ envelope of the L IR − T d relation for local IR galaxies in SDSS (excluding AGNs) adopted from Hwang et al (2010 in prep).…”
Section: Comparison With Smgsmentioning
confidence: 99%
“…Therefore, a relation consistent with the local one is an indication of star formation dominating both the IR and radio emissions. There is growing evidence that the correlation holds at redshifts z 1 (Garrett 2002;Gruppioni et al 2003;Appleton et al 2004;Boyle et al 2007;Marleau et al 2007;Vlahakis et al 2007;Yang et al 2007). At higher redshifts sample sizes are small making it difficult to draw robust conclusions (Appleton et al 2004;Kovács et al 2006;Beswick et al 2008;Ibar et al 2008;Sajina et al 2008;Garn et al 2009;Murphy et al 2009;Murphy 2009;Rieke et al 2009;Seymour et al 2009;Younger et al 2009b;Sargent et al 2010).…”
Section: Introductionmentioning
confidence: 99%